2015
DOI: 10.1007/s10529-015-1950-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Bacillus subtilis to enhance the production of tetramethylpyrazine

Abstract: This study provides valuable information to enhance the TTMP productivity of mutagenic strains through gene manipulation and fermentation optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…The TTMP biosynthetic pathway can be divided into two steps: first, accumulation of the precursor acetoin and ammonium; second, spontaneous condensation to form TTMP (Fig. ) . The first step is the enzymatic biogenic pathway, while the second step is a non‐enzymatic spontaneous reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TTMP biosynthetic pathway can be divided into two steps: first, accumulation of the precursor acetoin and ammonium; second, spontaneous condensation to form TTMP (Fig. ) . The first step is the enzymatic biogenic pathway, while the second step is a non‐enzymatic spontaneous reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The result was similar to that of published reports, which showed that TTMP was mainly produced from Bacillus spp. . The high TTMP production Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MH_Daqu of GujingTribute does contain Bacillus licheniformis, but this strain only occupies 0.68% in all MH_Daqu bacteria, while in Maotai Daqu Bacillus licheniformis is the most dominant species. This may explains why Maotai has a higher concentration of TTMP than other types of liquor [22][23].…”
Section: Relationship Between Daqu and Liquor Aroma Molecules'originmentioning
confidence: 97%
“…Tetramethylpyrazine (TTMP, C 8 H 12 N 2 , CAS NO. 1124-11-4) is a nitrogenous crystalline compound that shows the flavor of toast, grilled meat and nuts [1][2][3]. It is widely used as an important additive to promote the flavor of food under the regulation of NO.…”
Section: Introductionmentioning
confidence: 99%